Harmonization of Universality and Cultural Relativism in International Law (Lembaga Contrarius Indonesia, 2026)
International conferences on civilization and human rights (HAM) have played a strategic role in the development of modern international law, particularly in harmonizing the tension between the principle of the universality of human rights and cultural relativism. Since the 1993 Vienna Declaration, these international forums have reaffirmed the universal nature of human rights while recognizing cultural diversity as a contextual factor in their implementation. The conferences' outcomes, while often in the form of soft law, have had significant normative implications: strengthening customary international norms, providing interpretive guidance for human rights treaty bodies, expanding the agenda of new rights such as the right to development and the environment, and reconstructing the concept of state sovereignty into a responsibility to protect. On the other hand, challenges remain, including ambiguity in the formulation of declarations, gaps in implementation, and the risk of states misusing cultural relativism to justify repressive practices. Overall, however, international conferences function as normative engines that maintain the dynamics of international law, ensuring it remains responsive, inclusive, and aligned with the demands of global civilization. Thus, the conferences' normative implications not only strengthen universal standards but also enrich the diversity of sources of international law, while ensuring a balance between basic human rights principles and diverse socio-cultural.